Peduncle Necking in Rosa hybrida Induces Stress-Related Transcription Factors, Upregulates Galactose Metabolism, and Downregulates Phenylpropanoid Biosynthesis Genes - Lear, Bianca; Casey, Matthew; Stead, Anthony D.; Rogers, Hilary Joan (Frontiers in Plant Science, 2022)
Roses are highly valued as cut flowers worldwide, but have limited vase life. Peduncle bending ‘bent neck’ or ‘necking’ is a major cause of reduced vase life especially in some cultivars. Necking is thought to be caused either by an air embolism or accumulation of microorganisms at or within the stem end, blocking the xylem vessels and preventing water uptake. However, the underlying mechanisms of necking are poorly understood. Here RNAseq analysis was applied, to compare gene expression across three stages of peduncle necking (straight, <90° and >90°), in the necking-susceptible Rosa hybrida cultivar H30. Most gene expression change was later in bending and there was, overall, more down-regulation than up-regulation of gene expression during necking. Photosynthetic, starch and lignin biosynthesis genes were all down-regulated, while genes associated with galactose metabolism, producing raffinose and trehalose, both related to osmoprotection, were up-regulated. Genes associated with starch breakdown, autophagy and senescence were also up-regulated, as were most NAC and WRKY transcription factors, involved in stress and senescence regulation. Microscopy showed cellular collapse in the peduncle. These data support a possible mechanism whereby a reduction in water transport leads to cellular collapse in the peduncle, accompanied by upregulation of senescence and drought responses.